The Effects of a Theoretically-Grounded Gamified E-Learning Module on Motivation and Learning Outcomes in an Educational Technology Course: A Mixed-Methods Study - Siska, Jumiati; Kristiawan, Muhammad; Yulianti, Liza (PPSDP International Journal of Education, 2025)
This study investigates the integration of gamification into the theoretical design of e-learning within educational technology courses, with the primary objective of enhancing student motivation and learning outcomes. Employing a mixed-methods approach, the research gathered quantitative data through pre- and post-intervention assessments. This was complemented by qualitative feedback from participants engaging with a specially designed gamified e-learning module. Results demonstrate a significant increase in learner engagement and improved academic performance when compared to traditional e-learning formats. A key novelty of this study lies in its emphasis on the theoretical framework of e-learning design, specifically highlighting gamification elements tailored to the content of educational technology. The findings suggest that incorporating gamified strategies can effectively address motivational challenges and foster deeper understanding in virtual learning environments. This research offers evidence-based design guidelines for educators and instructional designers, facilitating the implementation of gamification in theoretical course contexts and ultimately contributing to the development of more effective and engaging digital education.